2021
DOI: 10.1016/j.celrep.2021.109727
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 deficiency alters activation of microglia subsets in traumatic brain injury

Abstract: Highlights d TBI elevates distinct phenotypes of microglia, macrophages, and dendritic cells d Ccr2 deficiency alters cell proportions and reduces ISG expression in microglia d TBI induces crosstalk between microglia and circulating monocytes d Preclinical translational studies to target human CCR2 after TBI improves outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 70 publications
1
25
0
1
Order By: Relevance
“…Whether indeed the high VLCFA levels in X-ALD macrophages amplify their ability to infiltrate the brain parenchyma upon onset of neuroinflammation remains to be clarified. Among the upregulated genes, CCR2 encodes the main chemokine receptor required for monocyte migration from the bone marrow to inflammatory sites and plays a key role in the damaging effects of neuroinflammation following traumatic brain injury [ 64 , 65 ]. Increased levels of CCR2 and CCL7 are not only observed in X-ALD macrophages, but have also been found in inflammatory brain lesions of X-ALD patients [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether indeed the high VLCFA levels in X-ALD macrophages amplify their ability to infiltrate the brain parenchyma upon onset of neuroinflammation remains to be clarified. Among the upregulated genes, CCR2 encodes the main chemokine receptor required for monocyte migration from the bone marrow to inflammatory sites and plays a key role in the damaging effects of neuroinflammation following traumatic brain injury [ 64 , 65 ]. Increased levels of CCR2 and CCL7 are not only observed in X-ALD macrophages, but have also been found in inflammatory brain lesions of X-ALD patients [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a regulatory interaction between SOCS proteins and IRF7 in a way that SOCS1 and SOCS3, induced by TLR7 in human plasmacytoid dendritic cells, promote IRF7 proteasomal degradation ( 63 ). Interestingly, application of antagonistic human (h)CCR2 small molecule inhibitor after traumatic brain injury to hCCR2 knock-in mice reduced the expression of Irf7 and mitigated loss of cognitive functions, improving disease outcome ( 64 ). A common marker of myeloid cells Itgam (CD11b), listed under the Staphylococcus aureus infection pathway gene set, was overexpressed in the CCR2 hi compared to the CCR2 lo OCP subset.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that CNS-resident macrophages could quickly generate context-dependent subsets, guided by the dynamics of molecule expression during neuroinflammation ( 19 ). Another study found that a deficient C-C chemokine receptor-2 (Ccr2) after TBI will reduce the expression of the IFN-responsive gene (IRF7), which will shape our understanding in finding the targets from the diversity and crosstalk of neuroinflammation ( 30 ). Therefore, permanent changes in the CNS molecular expression may explain the immune heterogeneity observed in patients with TBI.…”
Section: Triggering Signalmentioning
confidence: 99%